2009
DOI: 10.1111/j.1600-0560.2009.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of laminin in basal cell carcinoma

Abstract: Cytoplasmic and basement membrane laminin is important in the pathogenesis and invasion of BCC. Most laminin was in basement membrane zone (BMZ), and the more differentiated the tumor, the more cytoplasmic and BM staining it expressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…These results are in accordance with previous studies by Tosios et al .,[ 8 ] Souza et al .,[ 7 ] and Mostafa et al .,[ 9 ] where positive continuous staining of laminin was observed around the basement membrane. This indicates that the cells adjacent to basement membrane and the tumor cells secrete laminin.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with previous studies by Tosios et al .,[ 8 ] Souza et al .,[ 7 ] and Mostafa et al .,[ 9 ] where positive continuous staining of laminin was observed around the basement membrane. This indicates that the cells adjacent to basement membrane and the tumor cells secrete laminin.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, alterations in BM proteins expression contribute to development and progression of tumors. 13,14 Expression of cytoplasmic and BM laminin was increased with the degree of tumor cell differentiation in basal cell carcinoma. 14 Loss of collagen type IV has been observed in invasive prostate cancer.…”
Section: Introductionmentioning
confidence: 98%
“…13,14 Expression of cytoplasmic and BM laminin was increased with the degree of tumor cell differentiation in basal cell carcinoma. 14 Loss of collagen type IV has been observed in invasive prostate cancer. 13 BM proteins appear to play an important role in odontogenic tumors since many BM proteins are expressed in several types of odontogenic tumors.…”
Section: Introductionmentioning
confidence: 98%
“…The authors of the previous study also showed that patients with diffuse expression had a poorer prognosis than patients with the peripheral expression. Similar to SCC, the majority of cases of basal cell carcinoma also showed cytoplasmic expression of laminin‐5 in a recent study 21 …”
Section: Discussionmentioning
confidence: 59%